Relationships between somatic anxiety, cognitive anxiety, self-efficacy, and emotional intelligence levels in university physical education students - Mercader-Rubio, Isabel; Gutiérrez Ángel, Nieves; Silva, Sofia; Moisão, Ana; Brito-Costa, Sónia (Frontiers in Psychology, 2023)
One of the most studied topics nowadays, from psychology in general, and from sport psychology, is anxiety. In fact, research on anxiety has been approached from various theoretical perspectives ranging from psychoanalysis, behaviorism, or more recently, those theories that take into consideration the importance of affective, rational, and emotional processes. The aim of this study is to analyze the levels of anxiety and emotional intelligence, and their relationship. The sample is composed of 165 university physical education students with a mean age of 20.33 years (SD = 3.44), (70.9% male and 27.9% female). We used the CSAI-2 questionnaire (to measure cognitive anxiety, somatic anxiety, and self-confidence), and the TMMS-24 (to measure emotional intelligence). The main findings of this research highlighted the presence of significant correlations between emotional clarity and emotional regulation, self-confidence, cognitive anxiety, and somatic anxiety. Therefore, we conclude that sporting performance is influenced by various variables of different kinds, including emotions, and highlight the importance of the incorporation of the emotional component in the field of sport.